Mimimo-Flashcard: Vocabulary Learning Media Based on the Mimicry Memorization Method - Abdul Hafidz bin Zaid; Agus Yasin; Nur Hanifatus Sholeha; Azhar Amir Zein (IAIN Salatiga, 2022)
The Mimicry-Memorization Method is considered one of the foreign language teaching methods, particularly in teaching vocabularies. It relies on repeating and remembering. The foremost advantages of this method are its’ ability to transfer various kinds of vocabularies, besides it is also last longer in the students’ memory, and is low budget. However, this research assumed that continuous repetition and habituation will cause boredom and even reduce students’ interest in learning a language. So, the study was aimed at designing the learning media based on the Memorization method in the form of flashcards to make learning prosses more fun. This research applied the Research and Development (RD) procedure with partially on the Analysis, Design, and Development. The data was collected through the observation, interviews, and distributing questionnaires to the teachers and students of the 12th-grade at MAN 10 Jombang. The result showed that the design of the mimimo-flashcard consists of hand-drawn images in the affixed to the-card. It has 10 themes with 9 related-vocabularies for each with 90 vocabulary words in total. The learning media validation from each material’s expert and design’s expert showed 84% and 90% and can be categorized as good and decent. The calculation result of the trials to determine the product's effectiveness in mastering vocabulary for both the Experiment and Control classes was considered effective with sig. (2-tailed) sig.0.05 = 0.000.